Provenance determines salinity tolerance and germination requirements of the multipurpose tree Prosopis juliflora seeds. Issue 4 (2nd October 2021) - El-Keblawy, Ali; Aljasmi, Mariam; Gairola, Sanjay; Mosa, Kareem A.; Hameed, Abdul
Abstract: Information about seed source effects on germination and stress tolerance of the multipurpose exotic Prosopis juliflora (Sw.) DC. is scarce. Here, we investigate the influence of seed provenance on salinity tolerance and germination requirements of P. juliflora . Seeds collected from saline (SH) and nonsaline (SNH) habitats were treated with different NaCl concentrations (0–600 mM) and incubated in two photoperiods and three thermoperiod regimes. The results showed that tolerance of seeds from SH and NSH to salinity depended on thermoperiod, but not on photoperiod or interactions between photoperiod with both NaCl and thermoperiod. Germination of seeds from the two habitats did not differ significantly across thermoperiods in control and 200 mM NaCl. However, in 400 and 600 NaCl, germination was significantly greater for seeds from NSH than those from SH at lower thermoperiod in both light and darkness; whereas the reverse was true at higher temperatures in light. Seed germination of both habitat types was significantly lower at higher than at both lower and intermediate thermoperiods in all salt solutions, but the difference was more pronounced at higher salinities. Germination recovery failed in darkness at all photoperiod and thermoperiod regimes. Partial germination recovery happened only for seeds that failed to germinate in 400 mM NaCl in light and intermediate thermoperiod. Germination was significantly faster for seeds from SH than from NSH at higher salinities. The results emphasize the importance of considering the seed source for the restoration of salt-affected lands.